International corporate governance - John, Kose; Makhija, Anil K.; Ferris, Stephen P. (Advances in financial economics ;, 2015)
Advances in Financial Economics, volume 18, will present research on corporate governance both in the US and globally. Papers will deal with the role played by boards of directors, internal organization design and governance mechanisms, franchise agreements, the effect of regulation and policy, the market for corporate control, and strategic alliances. The volume will aim at providing a deeper understanding of corporate governance practices, trends, innovations and challenges using international data.